ANALISIS FAKTOR KESULITAN BELAJAR BAHASA ARAB DI MADRASAH ALIYAH SIDOARJO - Mubarroq, Iqbal Sulthon; Arifin, Moch. Bahak Udin By (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Arabic language subjects have long been implemented in Indonesia, especially at the Madrasah Aliyah (MA) level. However, the learning outcomes set have not been achieved. The purpose of this study is to analyze the difficulties of learning Arabic in MA. This type of research uses descriptive qualitative research method. The main data source was obtained by making direct observations in the field, namely the teacher and MA Darul Fikri Sidoarjo. The data collection techniques used are interviews, observation, documentation. The results of research conducted by researchers at Madrasah Aliyah (MA) Darul Fikri Sidoarjo in analyzing students' difficulties in understanding Arabic language subjects in class X Azhary, found that there are factors that cause difficulties experienced by students. These factors are the first internal factor, Mastery of vocabulary (mufradat), second, difficulty pronouncing Arabic, third lack of motivation, and external factors, first, learning media, second, learning methods, third, environmental factors. Efforts made by teachers at MA Darul Fikri Sidoarjo Islamic Boarding School in Arabic language subjects, namely, providing motivation and evaluation in Arabic language learning, to overcome learning difficulties show a pretty good effort. This can be seen from the teacher's efforts in overcoming learning difficulties, including using good and interesting learning methods and media